Management Strategies of Professional Zakat Funds for Mustahiq Family Welfare By Amil Zakat Body - Muhammad Iqbal; Rusli Rusli; Musyahidah Musyahidah (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2019)
This research deals with a professional zakat fund management strategy for mustahiq family welfare by Zakat Amil Body of Palu City Badan Amil Zakat. This research is qualitative research that tried to reveal and interpret this developing phenomenon. This is a case study that used such data collection techniques such as observation, interview, and documentation, while data analysis includes data reduction, presentation, and verification which ends with checking the validity of the data with the source triangulation method. The result showed that zakat collection units receive all kinds of charity such as infaq, sadaqah, as well as profession zakat that muzakkiwill to pay. Second is direct acceptance; that is, a zakat payer comes directly to the Baznas Office to hand over zakat, infaqand sadaqah (ZIS) to the officers in Baznas. The distribution is carried out in two ways: first, mustahiqs are given what they need in terms of daily basic necessities; secondly, aid is given to mustahiqs who have business to help them develop their business.